ANALISIS PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN BERAS ORGANIK DI KABUPATEN BLITAR - Anggi Anggraeni; Yuhanin Zamrodah; Luhur Aditya Prayudi (Universitas Islam Balitar, 2022)
The purpose of this study is to determine the characteristics of consumers in making organic rice purchase decisions. Specified criteria: by age, gender, education, occupation, income, number of family members, time of consumption, and amount of consumption ever made. The study also aims to find out what consumer behavior factors can influence the purchasing decision of organic rice in the research area. The population used is consumers who have purchased organic rice and the technique used is Non Probability sampling using the Purposivve Sampling method. The results showed that independent variables showed that they were valid and real and had passed the classical assumption test. Furthermore, social variables partially affect the purchasing decision of organic rice. Furthermore, psychological, personal, social, and cultural variables have a simultaneous significant effect on organic rice purchasing decisions.